(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
If an English student from twenty years ago walked onto a high school or university campus today, they might feel like they need a translator. They wouldn’t just hear standard English; they would hear a fast-moving, highly visual dialect shaped by TikTok, memes, and online gaming.